SALES SYSTEM DESIGN IRON / STEEL IN PT. TOBU INDONESIA STEEL - Jeje Jaelani; Sunarto Usna, Drs, MMSI (Jurnal Sistem Informasi, 2001)
System sales at PT. Tobu Indonesia Steel at this time still wore a manual system, so there are still many shortcomings. Disadvantages include a delay and the lack of accurate data processing, especially for sales systems iron / steel. Sales system design of iron / steel in proposing, its implementation will be realized by using a computer. This system can offer several advantages such as speed up the processing, data storage more reliable, so it can provide accurate information, which in turn will result in the performance of an effective and efficient.